A Clinical Randomized Controlled Trial of Acupuncture Treatment of Gastroparesis Using Different Acupoints - Wu Xuefen; Li Ping; Liu Li; Chen Xiaoli; Zenghui Yue (Pain Research and Management)
Objective. To explore the effect of “selecting acupoints by site” on the synergy effect of “acupoint compatibility” according to the clinical efficacy of acupuncture treatment of patients with gastroparesis. Methods. A total of 99 patients who met the diagnostic criteria for gastroparesis were enrolled in 3 clinical centers and randomly divided into group A (33 cases), group B (33 cases, 1 case of shedding), and group C (33 cases, 1 case of shedding). In group A, acupuncture was performed at Zhongwan (CV 12) and Zusanli (ST 36); in group B, acupuncture was performed at Neiguan (PC 6) and Zusanli (ST 36); in group C, acupuncture was performed at nonacupoint and Zusanli (ST 36). Treatment was performed for 30 minutes every day, 5 days as a course of treatment. There were 2 days off between courses and three courses in total. Differences in a main symptom index of gastroparesis (GCSI) scores, 9 symptom scores, and a health questionnaire (SF-36) were compared between each group before and after treatment and 4 weeks after the end of treatment. The difference of gastric emptying rate was compared before and after treatment. Results. The GCSI scores of each group after treatment and at follow-up were significantly lower than those before treatment (P<0.01), and the reduction in group A was greater than that of groups B and C (P<0.01). The score of each symptom was meaningfully lower than that before treatment (P<0.01 or P<0.05). The effect was best in group A, followed by group B. After treatment, the barium meal in the stomach of the three groups was significantly reduced compared with before treatment (P<0.01). There was no statistical difference between the groups. The results of SF-36 showed that acupuncture treatment can improve health status, to a certain extent, and there was no significant difference in the three groups. Conclusion. (1) Acupuncture is an effective method for the treatment of gastroparesis. (2) The combination of Zhongwan (CV 12) with Zusanli (ST 36) showed the most promising effect on relief of the symptoms in patients with gastroparesis. (3) “Selecting acupoints by site” is the key factor affecting the synergy effect of “acupoint compatibility.” This trial was registered with the International Center for Clinical Trials (registration no. NCT02594397).